2021 ELSO Adult and Pediatric Anticoagulation Guidelines. Issue 3 (March 2022) - McMichael, Ali B.V.; Ryerson, Lindsay M.; Ratano, Damian; Fan, Eddy; Faraoni, David; Annich, Gail M.
Abstract : Disclaimer: These guidelines for adult and pediatric anticoagulation for extracorporeal membrane oxygenation are intended for educational use to build the knowledge of physicians and other health professionals in assessing the conditions and managing the treatment of patients undergoing ECLS / ECMO and describe what are believed to be useful and safe practice for extracorporeal life support (ECLS, ECMO) but these are not necessarily consensus recommendations. The aim of clinical guidelines are to help clinicians to make informed decisions about their patients. However, adherence to a guideline does not guarantee a successful outcome. Ultimately, healthcare professionals must make their own treatment decisions about care on a case-by-case basis, after consultation with their patients, using their clinical judgment, knowledge and expertise. These guidelines do not take the place of physicians' and other health professionals' judgment in diagnosing and treatment of particular patients. These guidelines are not intended to and should not be interpreted as setting a standard of care or be deemed inclusive of all proper methods of care nor exclusive of other methods of care reasonably directed to obtaining the same results. The ultimate judgment must be made by the physician and other health professionals and the patient in light of all the circumstances presented by the individual patient, and the known variability and biological behavior of the clinical condition. These guidelines reflect the data at the time the guidelines were prepared; the results of subsequent studies or other information may cause revisions to the recommendations in these guidelines to be prudent to reflect new data, but ELSO is under no obligation to provide updates. In no event will ELSO be liable for any decision made or action taken in reliance upon the information provided through these guidelines.